Distinguishing Health from Pathology. Issue 5 (23rd August 2021) - Thorell, Amanda
Abstract: This essay provides an account of how to distinguish between health and pathology of trait tokens in medical theory. It (1) proposes to distinguish between two health/pathology concepts—health/pathology pertaining to survival and health/pathology pertaining to reproduction. It (2) defines measures for survival-efficiency and reproduction-efficiency of performances of physiological functions. It (3) provides an account of how, using the efficiency measures, to draw the line between health and pathology. The account draws, but seeks to improve, on Christopher Boorse's biostatistical theory. In relation to that theory, the suggested account has the advantages (1) that it defines efficiency and (2) that it harmonizes with judgments in medical theory in cases of common diseases and "normal aging." Furthermore, the essay argues against a competing idea of how to improve on the biostatistical theory, advocated by Peter Schwartz and Daniel Hausman.